Pelatihan Seni Tari Kreasi Baru Bagi Guru SD di Kecamatan Jabung Kabupaten Malang - Denna Delawanti Chrisyarani; Ratih Kartika Werdiningtiya (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2018)
This service aims to improve the ability of teachers in the art of dance and can improve the learning of dance both intra and ekstrakurikuler in each school District Jabung. Activities ranging from first up to seven the session on 6-8 October 2017 at 08.00-16.00 began delivering material insights into art education, basic dance malangan motion, range of motion dance bantengan parts 1 to 3, followed by create design patterns floors and practice. The results of the implementation of the activities have been implemented according to the plan, it is expected that the teacher can innovate in the learning of dance, what has been accepted teacher applied in the learning that they carry out.